"Neither it had social work components nor experiential": Students' perspectives of online fieldwork practice during COVID‐19 in India. Issue 3 (30th June 2022) - Negi, Dandub Palzor; E P, Abdul Azeez
Abstract: This paper explores social work students' perspectives of online fieldwork practice that emerged due to sudden disruption in field placement as a result of the outbreak of COVID‐19 in India. We have recruited and interviewed 32 Master's students from five north‐Indian universities to participate in the research. The study's findings highlight ill‐equipped agencies lacking social work components in online/virtual field placement. Also, ethical dilemmas in working virtually, disconnectedness from the field, and superficial supervision were experienced by the students. The study result implies the urgent need to develop and innovate a pedagogical approach to deal with uncertainties and crises like the COVID‐19.